2020
DOI: 10.3892/ijmm.2020.4790
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and SARS‑CoV‑2: A molecular modeling study of Zn interactions with RNA‑dependent RNA‑polymerase and 3C‑like proteinase enzymes

Abstract: RNA-dependent RNA-polymerase (RdRp) and 3C-like proteinase (3CL pro ) are two main enzymes that play a key role in the replication of SARS-CoV-2. Zinc (Zn) has strong immunogenic properties and is known to bind to a number of proteins, modulating their activities. Zn also has a history of use in viral infection control. Thus, the present study models potential Zn binding to RdRp and the 3CL pro . Through molecular modeling, the Zn binding sites in the aforementione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 71 publications
1
48
0
Order By: Relevance
“…Similar conclusions have been also drawn in various recent reviews aimed at assessing the potential positive role of zinc in COVID-19 treatment ( Joachimiak, 2021 ; Celik et al, 2020; de Almeida Brasiel, 2020; Name et al, 2020 ; Pormohammad et al, 2021 ; Rahman and Idi, 2020). In another recent review on the role of nutritional supplements as potential therapeutic adjuvants in COVID-19, Costagliola et al (2021) concluded that the supplementation of vitamin D, probiotics, lactoferrin and zinc, might be useful as an adjuvant treatment in COVID-19, as well as in the prevention of viral spreading.…”
Section: Essential Trace Elements and Covid-19supporting
confidence: 77%
“…Similar conclusions have been also drawn in various recent reviews aimed at assessing the potential positive role of zinc in COVID-19 treatment ( Joachimiak, 2021 ; Celik et al, 2020; de Almeida Brasiel, 2020; Name et al, 2020 ; Pormohammad et al, 2021 ; Rahman and Idi, 2020). In another recent review on the role of nutritional supplements as potential therapeutic adjuvants in COVID-19, Costagliola et al (2021) concluded that the supplementation of vitamin D, probiotics, lactoferrin and zinc, might be useful as an adjuvant treatment in COVID-19, as well as in the prevention of viral spreading.…”
Section: Essential Trace Elements and Covid-19supporting
confidence: 77%
“…Zinc is a trace element that plays a role in the development and function of the immune system exhibiting direct or indirect anti-viral properties [ 13 , 14 ]. High intracellular zinc levels were reported to stall the replication of coronavirus (SARS-CoV-2) and influenza virus that caused the severe acute respiratory syndrome [ 14 16 ]. Some reports demonstrate the synergistic effect of zinc with anti-viral therapy in SARS-CoV-2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of relevance, replication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) also needs two essential enzymes, RdRp and 3C-like proteinase (3CLpro). The zinc-binding sites were shown to be conserved in RdRp and 3CLpro by molecular modeling [20] . Though exact mechanisms are not yet defined, zinc-binding can reduce the enzymatic activities of 3CLpro and RdRp to inhibit viral replication [19] .…”
Section: Zinc: An Antiviral Nutrientmentioning
confidence: 99%